The left-handed booksellers of London - Nix, Garth (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2020)
A girl's quest to find her father leads her to an extended family of magical fighting booksellers who police the mythical Old World of England when it intrudes on the modern world. From the bestselling master of teen fantasy, Garth Nix.